A truncated variant of the ribosome-associated trigger factor specifically contributes to plant chloroplast ribosome biogenesis - Fabian Ries; Jasmin Gorlt; Sabrina Kaiser; Vanessa Scherer; Charlotte Seydel; Sandra Nguyen; Andreas Klingl; Julia Legen; Christian Schmitz-Linneweber; Hinrik Plaggenborg; Jediael Z. Y. Ng; Dennis Wiens; et al. (Nature Communications)
Abstract Molecular chaperones are essential throughout a protein’s life and act already during protein synthesis. Bacteria and chloroplasts of plant cells share the ribosome-associated chaperone trigger factor (Tig1 in plastids), facilitating maturation of emerging nascent polypeptides. While typical trigger factor chaperones employ three domains for their task, the here described truncated form, Tig2, contains just the ribosome binding domain. Tig2 is widely present in green plants and appears to have acquired an entirely different task than co-translational nascent polypeptide folding. Tig2 deletion results in remarkable leaf developmental defects of cold-exposed Arabidopsis thaliana plants and specific defects in plastidic ribosomes. Our data indicate that Tig2 functions during ribosome biogenesis by promoting the maturation of the large subunit. We hypothesize that Tig2 binding to the ribosomal tunnel-exit surface aids protecting this sensitive surface during assembly. Tig2 illustrates a fascinating concept of how a chaperone domain evolved individually, serving a completely different molecular task.